Quick Boot : a Guide for Embedded Firmware Developers, 2nd edition - Dice, Pete (De|G Press, 2017)
Quick Boot is designed to give developers a background in the basic architecture and details of a typical boot sequence. More specifically, this book describes the basic initialization sequence that allows developers the freedom to boot an OS without a fully featured system BIOS. Various specifications provide the basics of both the code bases and the standards. This book also provides insights into optimization techniques for more advanced developers. With proper background information, the required specifications on hand, and diligence, many developers can create quality boot solutions using this text. Pete Dice is Engineering Director of Verifone, where he manages OS Engineering teams in Dublin, Ireland and Riga Latvia. Dice successfully launched Intel® Quark™, Intel's first generation SoC as well as invented the Intel® Galileo™ development board and developed a freemium SW strategy to scale Intel IoT gateway features across product lines. He is also credited with architecting the "Moon Island" software stack and business model.- Resumé vydavatel
Keywords: BIOS (rozhraní); vývoj softwaru; BIOS (interface); software development; firmware; elektronické knihy; příručky; electronic books; handbooks and manuals